Relative age effects in Japanese athletes - Nakata, H.; Sakamoto, K. (The Journal of Physical Fitness and Sports Medicine, 2014)
`Relative age effect` (RAE) is considered a factor in successful sporting activities. That is, older children in a particular age group are more likely to achieve sporting success than younger ones. Many studies on RAEs have been conducted for the sports systems in North American and European countries. In this article, we elaborate on the RAEs in Japanese athletes of both male and female sports, the association of RAEs with number of years in school and with legal-gambling sports, and give a historical analysis of Japanese baseball. Since 1886, Japan has applied a unique age-grouping for education, which groups students with birthdays from April 1 to March 31 of the following year into the same age category. Therefore, April 1 is the beginning of each `new year`, and this specific calendar applies to the education system including elementary, junior high and senior high schools, university (college), as well as to government and private companies. Sports calendars also follow this system, and many professional sports such as baseball, soccer, basketball, and volleyball start the new season in April. Therefore, players born in April, May, and June should have a relative age advantage. We introduce the characteristics and phenomenon of RAEs in Japanese athletes, and discuss several problems that should be addressed in future studies.